Сучасні підходи до управління витратами промислових підприємств - Лаврик, У. В.; Бондик, К. Ю.; Lavryk, U.; Bondik, К. (КНТУ, 2013)
У статті проаналізовано сучасні методи управління витратами підприємства та встановлено необхідність індивідуального підходу до вибору систем управління витратами підприємств. In this article theoretical grounds are considered and methodical recommendations of selecting the costs management methods are presented. In the research the modern methods of cost management are analyzed and the necessity of individual approach is set to the choice of the existent systems of cost management of enterprises. Terms and factors that influence to the choice of methods for costs management methods are determined, as well as dependence between indicators of industrial enterprises costs and influence of methods usage on effectiveness of costs management. Practical use of the proposed recommendations will improve the efficiency of the management costs, which will boost the efficiency of the enterprise.
Modern approaches to cost management industrial enterprises
Keywords: витрати; підприємство; управління витратами; методи; ефективність; сharges; enterprises; cost management; methods; efficiency